SULFUR-BINDING IN RECENT ENVIRONMENTS: II. SPECIATION OF SULFUR AND IRON AND IMPLICATIONS FOR THE OCCURRENCE OF ORGANO-SULFUR COMPOUNDS - Hartgers W.A.; Lopez J.F.; Damste J.S.S.; Reiss C.; Maxwell J.R.; Grimalt J.O. (My University, 1997)
Speciation of iron and sulfur species was determined for two recent sediments (La Trinitat and Lake Ciso) which were deposited in environments with a high biological productivity and sulfate-reducing activity. In sediments from calcite ponds of La Trinitat an excess of reactive iron species (iron monosulfides, iron hydroxides) results in a depletion of reactive sulfur which is accompanied by a virtual absence of organo-sulfur compounds, both in low (LMW) and high molecular-weight (HMW) fractions. Small amounts of phytanyl and highly branched isoprenoid (HBI) thiophenes in the extract demonstrate that these molecules exhibit a higher reactivity towards reduced sulfur species as compared to detrital iron. Euxinic sediments from Lake Ciso are characterised by an excess of reduced sulfur species which can rapidly trap reactive iron. High concentrations of H2S results in the formation of organo-sulfur compounds which were encountered in both LMW and HMW fractions. The major part of the organic sulfur is bound to the carbohydrate portion of woody tissues, whose presence was revealed by a specific alkylthiophene distribution in the flash pyrolysate and by Li/EtNH2 desulfurisation of the kerogen which resulted in the solubilisation of the sulfur-enriched hemicellulose fraction. Relatively high amounts of sulfurised C25 HBI compounds in the sediment extract of Lake Ciso reflect the incorporation of sulfur into algal derived organic matter upon early diagenesis. The combined approach of the speciation of iron and sulfur species and the molecular analysis of sedimentary fractions demonstrates that abiotic sulfur binding to organic matter occurs at the earliest stages of diagenesis under specific depositional conditions (anoxic, stratified water column) in which an excess of reduced sulfur species relative to the amount of reactive iron is a controlling factor.